2017
DOI: 10.1371/journal.pone.0170436
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin Predicts Mortality in Critically Ill Patients

Abstract: BackgroundCritically ill patients admitted to a medical intensive care unit exhibit a high mortality rate irrespective of the cause of admission. Besides its role in fluid and electrolyte balance, vasopressin has been described as a stress hormone. Copeptin, the C-terminal portion of provasopressin mirrors vasopressin levels and has been described as a reliable biomarker for the individual’s stress level and was associated with outcome in various disease entities. The aim of this study was to analyze whether c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
4
11
1
Order By: Relevance
“…Nonetheless, the activation of this pathway, as reflected by copeptin, is closely related to the patients’ prognosis at and beyond the ICU. In agreement with prior studies in patients with acute illnesses that noted an association with short‐term mortality, our study confirmed the value of copeptin levels as a prognostic biomarker for the ICU mortality. More strikingly, copeptin plasma concentrations at the admission to the ICU even predicted the long‐term, overall mortality of critically ill patients in our study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nonetheless, the activation of this pathway, as reflected by copeptin, is closely related to the patients’ prognosis at and beyond the ICU. In agreement with prior studies in patients with acute illnesses that noted an association with short‐term mortality, our study confirmed the value of copeptin levels as a prognostic biomarker for the ICU mortality. More strikingly, copeptin plasma concentrations at the admission to the ICU even predicted the long‐term, overall mortality of critically ill patients in our study.…”
Section: Discussionsupporting
confidence: 92%
“…We conducted a large observational study, in which we prospectively enrolled 218 critically ill patients from our medical ICU, to determine the value of copeptin as a biomarker in the intensive care setting. In line with previous reports of patients with acute illnesses, critically ill patients had significantly higher circulating copeptin levels as compared to healthy controls. However, the disease entity (eg sepsis) or metabolic comorbidities that would affect copeptin levels in the chronic setting did not determine copeptin concentrations in critical illness.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations